Nonlinear THz conductivity in graphene - Mics, Zoltán; Jensen, Søren; Parvez, Khaled; Ivanov, Ivan; Tielrooij, Klaas Jan; Koppens, Frank H.L.; Feng, Xinliang; Müllen, Klaus; Bonn, Mischa; Turchinovich, Dmitry (Optics InfoBase Conference Papers, 2014)
We report the nonlinear THz conductivity of graphene. The heating of charge carriers by strong THz pulses results in a reduction of the high-frequency conductivity of graphene, in spite of reduced scattering for high-energy carriers. © 2014 OSA.
CRIS-Team Scopus Importer:2023-03-20